2003
DOI: 10.1161/01.cir.0000079162.69615.0f
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of D-Dimer Test for Recurrent Venous Thromboembolism After Anticoagulation Withdrawal in Subjects With a Previous Idiopathic Event and in Carriers of Congenital Thrombophilia

Abstract: Background-We have shown that normal D-dimer levels obtained after the discontinuation of oral anticoagulant treatment (OAT) has a high negative predictive value for recurrent venous thromboembolism (VTE). The aim of the present study was to assess the predictive value of D-dimer for recurrent VTE in subjects with a previous unprovoked event who are either carriers of inherited thrombophilia or not. Methods and Results-We prospectively evaluated 599 patients (301 males) with a previous VTE episode. They were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
2
11

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(225 citation statements)
references
References 29 publications
7
205
2
11
Order By: Relevance
“…Earlier prospective studies in patients with VTE [9][10][11][12] demonstrated that D-dimer levels have a strong predictive value for the occurrence of subsequent episodes. These studies suggested that D-dimer measurement may have a role in gauging the duration of anticoagulation in patients with VTE.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier prospective studies in patients with VTE [9][10][11][12] demonstrated that D-dimer levels have a strong predictive value for the occurrence of subsequent episodes. These studies suggested that D-dimer measurement may have a role in gauging the duration of anticoagulation in patients with VTE.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 599 patients, elevated Ddimer levels were found in 37% of individuals after discontinuing anticoagulation. 17 The probability of recurrence 2 years later was the highest (18%) in those patients with unprovoked DVT. In the PREVENT study, presence of a ddimer level of greater than 500 ng/mL 7 weeks post cessation of anticoagulation was associated with a 2-fold risk of recurrence.…”
Section: D-dimer Levelsmentioning
confidence: 95%
“…[27][28][29] Increased D-dimer levels were associated with a higher risk of subsequent recurrence. However, it is not yet known whether D-dimer levels or residual venous thrombosis have a role in adjusting the duration of oral anticoagulant therapy.…”
Section: Vitamin K Antagonistsmentioning
confidence: 97%